A narrative review of cognitive behavioural therapy in supporting bereaved adults with intellectual disability. (25th February 2020) - Lonergan, Aoife
Accessible summary: People with an intellectual disability may have feelings that are hard to manage when a loved one dies. People with an intellectual disability may not receive access to enough support to help them understand and manage difficult feelings when someone dies. Cognitive behavioural therapy is a therapy that can be adapted and may be useful to support people with intellectual disability when someone they love has died. Abstract: Background: As the life expectancy of adults with intellectual disability has increased, experience of familial bereavement is becoming more frequent. However, this group may not receive adequate information and support to enable them to understand and cope with the experience of loss. Method: This narrative review examined the impact of bereavement, the ability to engage in cognitive behavioural therapy (CBT) and learn skills to understand and cope with bereavement, in an intellectual disability context. Results: Findings indicated that the loss of someone close can render adults with intellectual disability at increased risk for additional mental health difficulties. Among variables associated with better death comprehension are higher levels of cognitive ability, adaptive behaviour skills and receptive language ability. However, research indicates that understanding the concept of death is not a requirement for experiencing the emotions associated with grieving. Findings indicated that the successful use of CBT for bereavement in people with intellectual disability requires adaptation, such as the use of visuals and preparatory training in relation to the CBT model. Conclusions: With adaptation, CBT may be beneficial in supporting adults with intellectual disability to understand and cope with bereavement. The lack of controlled studies available for review exploring the impact of CBT on bereavement and the lack of standardised measures available in a population intellectual disability limit this review's findings. Controlled studies examining the effectiveness of adapted CBT for bereavement in a population with intellectual disability are recommended.